ANXIETY OF ISABELLA SWAN ON LOOSING HER LOVE IN CHRIST WEITZ's NEW MOON MOVIE: A PSYCHOANALYTIC APPROACH - TUNJUNGSARI, APRILIANI DEVI (2010)
The major problem of this study is how the anxiety of the major character, Bella on loosing her love reflected in Christ Weitz's New Moon movie. The objective of this study is to analyze the movie based on its structural elements, and based on psychoanalytic approach. The benefits of the study are to give in the application of Psychoanalytic approach in literary study. The study belongs to the qualitative study. The object of the study is Isabella Swan's New Moon movie published in 2009 by Summit Entertainment. The primary data source is the main data obtained from all the images which form such like the scene of the movie itself and the texts which form such like words, phrases, and sentences in dialogues or monologues occurring in the movie related to the topic and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by note-taking for the texts and image-capturing for the images. The technique of data analysis used in this study is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, Bella is a girl who has a weak sense and feeling, the most comfortable girl feelings if she is in the top position of sadness is cry. Second, based on the psychoanalytic analysis, it is evident that in this movie, Isabella's life is directed by her ego, which is dominated by her id and also her superego.